KETERKAITAN KEBUDAYAAN ISLAM DENGAN KARAKTER ORANG JEPANG - Suparno ' (IZUMI, 2013)
Abstract   As a religion Islam has a teaching material integral and comprehensive in addition to containing the main teachings of shariah also motivate followers to develop Islamic culture. Culture that reflects Islamic values in them. Culture is based on the value of religious values will be able to produce a personality/character that positive. Japan is know as a country that has a high civilization characterized by a character with positive character inherent in Japanese society. Japan is not an Islimic state muslim even the minority, but if you see sometimes more islamic character of its people than even the majority muslim country like Indonesia. The purpose of this study is to reveal the value of islamic values in the character of Japanese society.   Key Word :  Islamic, Culture, Japanese and Character